Size-segregated Characteristics and Formation Mechanisms of Water-soluble Inorganic Ions during Different Seasons in Heshan of Guangdong, China - Bo Huang; Ting Gan; Chenglei Pei; Mei Li; Peng Cheng; Duohong Chen; Ridong Cai; Yujun Wang; Lei Li; Zhengxu Huang; Wei Gao; Zhong Fu; et al. (Aerosol and Air Quality Research)
Abstract To identify the characteristics, sources, and formation mechanisms of aerosol particles during pollution episodes in the Pearl River Delta, 24 sets of size-segregated samples were collected in Heshan during July 2014 and January 2015 using a 10-stage Micro-Orifice Uniform Deposit Impactor (MOUDI), and nine ions, viz., Na+, NH4+, K+, Mg2+, Ca2+, Cl−, NO2−, NO3−, and SO42−, were investigated. The Na+, Mg2+, and Ca2+ were mainly distributed in the coarse particles, and were mainly from soil, dust, and sea salt. The fine-mode K+ during winter was mostly generated by biomass burning. The coarse-mode Cl− originated from sea salt, whereas the fine-mode Cl− resulted from the conversion of NH4Cl to the particle phase. Both the SO42− and the NO3− exhibited unimodal distributions during winter but bimodal ones during summer. The coarse-mode SO42− and NO3− arose from sea salt and heterogeneous reactions, respectively. An increase in the nitrogen oxidation ratio (NOR) and a decrease in the sulfur oxidation ratio (SOR) were observed on polluted days, with the highest values occurring in the 0.56–1 µm particle size fraction. The formation of NO3− was chiefly related toµ homogeneous gas-phase reactions during winter and nocturnal heterogeneous reactions involving N2O5 during summer, whereas the formation of SO42− was driven by gas-phase oxidation in the 0.056–0.32 µm size range and aqueous oxidation in the 0.56–3.2 µm range. Additionally, the SOR and the NO2 concentration displayed a positive correlation in the 0.056–1.8 µm particle size fraction, indicating that the potential formation of SO42− via aqueous reactions was accelerated by NO2.